The Potential Role Of Thrombopoietin And Il-6 In The Thrombocytosis Effect Of Carica Papaya Leaves - Laila M Abdelrahim; Abdul Jalil SNS; Abu Seman Z; Zetty Nadia Mohd Zain; Fadlul Azim Fauzi Mansur; Noradilah Samseh Abdullah (JK Welfare & Pharmascope Foundation, 2024)
Volume :11 No: SPL4